2014
DOI: 10.1002/jlcr.3175
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated synthesis and coupling of [18F]FBEM to glutathione using the iPHASE FlexLab module

Abstract: Site-specific radiolabelling of peptides or antibodies using [(18) F]FBEM is often preferred over non-site-specific radiolabelling with [(18) F]SFB because it does not affect the affinity of the antibody to its target. Unfortunately, the synthesis of [(18) F]FBEM and its conjugation to thiol containing macromolecules requires some manual intervention, which leads to radiation exposure of the radiochemist. In this publication, we report on the complete automation of [(18) F]FBEM production and its subsequent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…36 Ackermann et al also reported the fully automated radiolabeling of the protein glutathione with [ 18 F] FBEM the thiol reactive prosthetic group on an iPHASE FLEX-Lab module, however no extension of this methodology to radiolabeling a clinically-relevant peptide was included in this paper. 37 Both methods required some form of manual intervention, and to our knowledge a fully automated procedure for the radiosynthesis of a clinically relevant uorine-18 radiolabeled peptide has yet to be reported. 4 Therefore, the goal of this work was to develop a fully automated 18 F-peptide radiolabeling synthesis and apply it to three clinically relevant peptides (YGGFL (1), cRGDyK (2), and Pyr-QKLGNQWAVGHLM (3)) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…36 Ackermann et al also reported the fully automated radiolabeling of the protein glutathione with [ 18 F] FBEM the thiol reactive prosthetic group on an iPHASE FLEX-Lab module, however no extension of this methodology to radiolabeling a clinically-relevant peptide was included in this paper. 37 Both methods required some form of manual intervention, and to our knowledge a fully automated procedure for the radiosynthesis of a clinically relevant uorine-18 radiolabeled peptide has yet to be reported. 4 Therefore, the goal of this work was to develop a fully automated 18 F-peptide radiolabeling synthesis and apply it to three clinically relevant peptides (YGGFL (1), cRGDyK (2), and Pyr-QKLGNQWAVGHLM (3)) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Further, we have recently reported the synthesis and evaluation of sulfonated versions of these peptides, Abbreviations: FP, 2-fluoropropionyl; NFP, 4-nitrophenyl 2fluoropropionate; PEG, polyethylene glycol; PET, positron emission tomography; RGD, arginyl-glycyl-aspartyl-containing peptide 2 and 4, which show favorable biodistribution. 22 Herein, we present the utility of the iPHASE Flexlab automated module for the routine preparation of the fluorine- 18 Figure 1). The full utilization of these valuable clinical agents requires the development of modular, automated radiochemical procedures capable of generating the final radiotracer in a single, programmable module with minimal human intervention.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the establishment of an automated radiosynthesis platform is crucial for the preparation of fluorine-18 labeled peptides such as [ 18 F]GalactoRGD 1 and [ 18 F]FPPRGD2 3. 22 Herein, we present the utility of the iPHASE Flexlab automated module for the routine preparation of the fluo- rine Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to develop the production of [ 18 F]FDHT for clinical use in our centre using the iPHASE technologies FlexLab module since it is ideally suited to the automation of complex radiosynthesis procedures …”
Section: Introductionmentioning
confidence: 99%
“…We chose to develop the production of [ 18 F]FDHT for clinical use in our centre using the iPHASE technologies FlexLab module since it is ideally suited to the automation of complex radiosynthesis procedures. 15,16 Materials and methods The HPLC system used for semi-preparative workup of [ 18 F]FDHT was a Knauer Smartline 1050 pump with a Smartline Manager 5050 for quaternary gradient capability. The Knauer UV detector 2520 (254 nm) and a CsI(Tl) crystal PIN diode radioactivity detector were used for the detection of compounds.…”
Section: Introductionmentioning
confidence: 99%